City Farm Garden : countering the impacts of urban expansion in a rural valley in the Western Cape through a gardening approach to place-making - Prinsloo, Johan N. (University of Pretoria, 2022)
Mini Dissertation (ML (Prof))--University of Pretoria, Pretoria, 2021.